Optimal exercise modality and dose for alleviating depressive symptoms in postmenopausal women: a systematic review and network meta-analysis of randomized controlled trials - Xu, Peiming; Guo, Rui; Yang, Lei; Ding, Junkai (Frontiers in Psychology, 2025)
ObjectiveAlthough physical exercise is widely recognized as an effective non-pharmacological intervention for depressive symptoms, the relative efficacy of different exercise modalities and the optimal dose for postmenopausal women remain unclear. This study aimed to determine the optimal exercise modality and dose for alleviating depressive symptoms in postmenopausal women through a systematic review and network meta-analysis (NMA), incorporating a model-based network meta-analysis (MBNMA) for dose–response relationships.MethodsFive major electronic databases (Web of Science, Cochrane Library, PubMed, EBSCO, and Embase) were searched for randomized controlled trials (RCTs) investigating the effects of exercise interventions on depressive symptoms in postmenopausal women. The risk of bias in included studies was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool. The NMA and dose–response MBNMA were conducted using R software.ResultsA total of 33 RCTs involving 2,607 participants were included. The NMA results showed that all four exercise modalities—resistance exercise (RE), mind–body exercise (MBE), aerobic exercise (AE), and combined exercise (CBE)—significantly alleviated depressive symptoms compared to the control group: RE (SMD = −0.90, 95% CI: −1.61 to −0.20), MBE (SMD = −0.75, 95% CI: −1.07 to −0.43), AE (SMD = −0.67, 95% CI: −0.93 to −0.42), and CBE (SMD = −0.63, 95% CI: −1.19 to −0.06). P-score rankings suggested that RE (p = 0.774) and MBE (p = 0.662) had the greatest therapeutic potential. The dose–response analysis revealed a significant U-shaped relationship, with a minimum effective dose of 183 METs-min/week and an optimal dose around 750 METs-min/week. The therapeutic effect tended to diminish beyond 1,130 METs-min/week. Among the modalities, MBE had the lowest effective dose threshold (164 METs-min/week).ConclusionPhysical exercise is a highly effective intervention for alleviating depressive symptoms in postmenopausal women, with resistance and mind–body exercises demonstrating the greatest therapeutic potential. The antidepressant effect of exercise follows a U-shaped dose–response relationship, with an optimal dose of approximately 750 METs-min/week. These findings provide robust evidence for clinicians to move beyond generic recommendations and to develop precise, individualized exercise prescriptions tailored to the specific needs and conditions of their patients.Systematic review registrationPROSPERO, identifier (CRD420251208430).